The Oxford handbook of divine revelation - Mezei, Balázs M.; Murphy, Francesca Aran; Oakes, Kenneth ca. 20./21. Jh. (Oxford handbooks, 2021)
"In this volume we have followed our important predecessors that produced overviews of the notion of divine revelation during the past decades. We have chosen the multidisciplinary way as an attempt to explain what divine revelation can mean in our time. The underlying idea is that the proper understanding of God's revelation can be given in the systemic way. The main parts of this work-the biblical, theological, philosophical, historical, scientific and cultural approaches-offer possibilities to perceive, conceive and assess divine disclosure. There are chapters dealing with the Biblical background of revelation; there are others that explain the delicate relationship between the Christian understanding of the fulfillment of revelation in Christ and the original revelation given to Moses, Abraham, and to the created whole in the act of creation. Other chapters explore the theological aspects of revelation beginning with the Trinitarian problematic to the realm of charismatic forms of revelation, including the Marian apparitions as unique examples of the reality of revelation in our days. The philosophical explorations of the problem of revelation show the importance of philosophical reflections on revelation today or on a historical scale. A radical understanding of revelation is the ultimate horizon of the reality of divine revelation, a horizon which connects philosophical, theological, Biblical and comparative approaches. Revelation-related forms in Hinduism, Buddhism, the Chinese tradition or African religions contribute to the better understanding of the important role of divine revelation in connecting cultures and religions around the globe. The notion of revelation in Judaism and Islam has the paramount role in any comparative understanding, which needs to be extended to the importance of our conceptions of revelation in view of European history, especially the Holocaust. This event appears a watershed in our contemporary reflections on revelation, because it triggered radical rethinking, reassessment and revaluation of traditional theological and philosophical conceptions"--